Attitude And Action Mother With Hiv Aids On Stigma And Discrimination People at Semarang City - M. Irwan Katili; Rini Indrati; Yeti Kartikasari (Jurnal LINK, 2012)
The purpose of this study to explore the attitudes and actions of mothers with HIV AIDS stigma and discrimination people in the city of Semarang. The research was conducted with a qualitative approach. As the population of mothers with HIV-AIDS is the number of 26 people, while the number of samples is 6 people for Mother PLWHA. To triangulate the source comes from a number of health personnel and the public a number of 3 people 6 people. The collection of data used interviews and Focus Group Discussions with the techniques Data Analysis used Interactive Models. The attitudes and actions of mothers living with HIV Stigma and discrimination against people is to avoid interacting with the community and need support from family, health professionals and peers (DKS)